COVID-19 and aerobic exercise: possible role of angiotensin converting enzyme 2 - Haidar Djemai; Rami Hammad; Ibrahim M. Dabayebeh; Saleh Hammad; Abdellah Merzouk; Xavier Coumoul; Philippe Noirez (BMC, 2022)
Highlights • Physical inactivity during COVID-19 lockdowns may damage health. • Risk of contamination by aerosols is higher during high-intensity urban outdoor exercise. • Angiotensin converting enzyme 2 (ACE2) could play key role in SARS-CoV-2 transmission during exercise. • How ACE2 serum concentration changes as function of exercise intensity and duration must be studied to elucidate role of this enzyme.